Financial Literacy Amongst Young People: When Does the Gender Gap Begin? - Alison Preston; Robert E. Wright (Institute of Labor Economics (IZA), 2022)
Using micro-data from the Household, Income and Labour Dynamics in Australia (HILDA) Survey, and the Oaxaca-Blinder decomposition technique, this paper contributes to knowledge on gender-gaps in financial literacy (FL) via a study of teenagers, emerging adults and young adults. The analysis suggests that important predictors of FL include schooling, high school-type, labour market activity and parental employment. There are large unexplained gaps, equal to 31.6%, 19.3% and 11.9% amongst those aged 15-19, 20-24 and 25-29, respectively. Very little of the gap may be explained by gender differences in human capital variables and other characteristics, including mathematics ability, cognitive ability and personality. The main conclusion is that the gap starts young and likely derives from gender stereotype beliefs.
Keywords: B54; D14; D31; G18; I30; J26; 330; financial literacy; gender gap in financial literacy; gender stereotypes; adolescence; Oaxaca-Blinder decomposition